Building Bridges : Perceptions and Realities About the English-speaking Communities of Quebec and their Relationship with French in Quebec and Bilingualism in Canada - Canada. Office of the Commissioner of Official Languages (2024)
The Office of the Commissioner of Official Languages (the Office of the Commissioner) has observed that, in recent years, the English-speaking communities of Quebec (ESCQ) have been the focus of much public discourse and debate in the province. Survey and census data indicate that, overall, the ESCQ are highly bilingual and value Canada’s broader linguistic duality, including the French language. The extent to which the general population is aware of these facets of the ESCQ is not clear, however, and the Office of the Commissioner wished to test the hypothesis that problematic myths may persist. In light of this context and with the modernization of the Official Languages Act by the federal government in 2023, which recognizes the need to “advance the existence of a majority-French society in a Quebec where the future of French is assured,” this research project is an opportunity to shed light on the relationship that the ESCQ have with the French language in Quebec and official bilingualism in Canada as a whole. This is also an opportunity to explore how Quebec’s English-speaking minority can be considered as bridge-builders or even as a potential ally of the promotion of French in Canada as a whole, with a view to developing a more constructive discourse that better acknowledges their contributions and, ultimately, deconstructs certain misperceptions.
Keywords: Official Language Minority Community (OLMC)

QFHSA Board of Directors Shocked at CAQ Attack on McGill, Concordia, and Bishop's - Quebec Federation of Home and School Associations (QFHSA) (2023)

Committee Adopts Series of Surprise Changes Regarding Bilingualism in Quebec Judicial Appointments - Quebec Community Groups Network (QCGN) (2022)

Our Local Pioneers! : A Podcast on the Collaboration between Francophones and Anglophones in the Outaouais and their Contributions to Quebec Society, from Yesterday to Today - Nivischiuk, Jeanne (2022)

French-language Support for Québec's English-speaking Professionals - Juste, Catherine-Laure (Provincial Employment Roundtable (PERT), 2022)
French-language barriers can be a challenge for professionals who are English speakers and must practice their profession in accordance with French-language policies. Despite high levels of English-French bilingualism among Québec’s English speakers, French remains a challenge for some who require additional profession-specific French-language training. Not only is French-language proficiency a requirement for membership in Québec’s professional orders, but professionals who do not meet language criteria must also pass a French-language competency exam administered by the Office québécois de la langue française (OQLF). Additionally, professional orders can mandate all their members to take French-language professional competency exams throughout their careers.

Bill 96 & Employment of English Speakers in Québec - Provincial Employment Roundtable (PERT) (2022)
On May 24, 2022, Québec’s National Assembly passed Bill 96, An Act Respecting French, the Official and Common Language of Québec. The bill, which presents significant modifications to The Charter of the French Language (Bill 101), as well as other existing legislation, was passed more than a year after it was introduced. On June 1, 2022, Bill 96 received royal assent and some of its clauses came into effect immediately. Other clauses of the bill will come into effect at later dates.

French-Language Training for the Workforce : A review of French-language training programs for the workforce in Québec - Provincial Employment Roundtable (PERT) (2022)
This report examines the status of French-language workforce programs (FLWPs) in Québec. FLWPs consist of language learning that is specifically designed to increase the integration of workers into the labour market by focusing on the vocabulary and language skills they need to improve their employability. In this report, we conducted an inventory of FLWPs that are available to French-language learners and identified the key needs, gaps and areas for improvement in the ecosystem.

Hats and High Tea : Local Collector to Share "Mobile Museum" in Bilingual Talk Highlighting the History of Fashion from 1940-1965, Followed by a Traditional English-style High Tea - Centre for Access to Services in English (CASE) (2021)

Resolution 2021-01 : Free French Instruction Services for all Who Request Them - Quebec Federation of Home and School Associations (QFHSA) (2021)

What Canadians Think About Learning English and French - Canada. Office of the Commissioner of Official Languages (2021)

What Canadians Think About Official Bilingualism and the Official Languages Act - Canada. Office of the Commissioner of Official Languages (2021)

Issues of Bilingual Education in Quebec's English-language Schools - Ciamarra, Nadine; Lamarre, Patricia; Donovan, Patrick; O'Donnell, Lorraine (Quebec English-speaking Communities Research Network (QUESCREN), 2021)
The percentage of Quebec’s population with French-English bilingual skills has steadily increased over the past decades, and this is the case for all Quebecers, regardless of language background (Turcotte, 2019). Quebec Anglophone youth, however, are the most bilingual, and become bilingual at a younger age than Francophone or Allophone youth. The explanation is simple: Quebec’s English-speaking parents have been able to rely on schools to develop their children’s bilingual skills, thanks to French immersion and other enriched French-secondlanguage programs (Lamarre, 1997, 2007, 2012; Magnan et al., 2018), and in some cases by crossing over to the French sector (Laperrière & Lamarre, 2006).
Keywords: Official Language Minority Community (OLMC)

Government Must Not Territorialize the Equality of Canada's Official Languages - Quebec Community Groups Network (QCGN) (2020)
Keywords: Official Language Minority Community (OLMC)

Secondary School Exchanges : A Promising Way of Fostering Bilingualism in the Next Generation - Lai, Edward; Orme, Charlie; Fleming, Scott (Y4Y Québec, 2018)
In Quebec, it is a basic fact that a solid grasp of the French language is essential to finding work, participating fully in the political process, and integrating into society. While statistics show that bilingualism is very common among the Englishspeaking minority, and especially so among youth, problems nonetheless arise. Young English-speakers frequently report that they do not feel confident enough in their ability to speak French, while others remark that their written French is not strong enough to land a job. Inadequate knowledge of French is a contributing factor to the higher unemployment rates experienced by young English- speakers. A lack of work, and a hampered ability to take part in public life in general, lead to the disenfranchisement of members of this community. Given the high demand among young English- speakers for more French-language training, policy makers must come up with new and creative ways of meeting the demand.

Active Offer : A Culture of Respect, a Culture of Excellence - Canada. Office of the Commissioner of Official Languages (2017)

Keeping the Door Open for Young English-speaking Adults in Québec : Language Learning in English Schools and Centres - Advisory Board on English Education (2016)
During a committee hearing in April 2015, Premier Philippe Couillard responded to a question from Mr. David Birnbaum (MNA for D’Arcy-McGee) about “what our government has done and plans to do to ensure that young anglophone Quebecers are full and valued participants in building our future,” by saying that he wanted to hear from the English-speaking community. About the same time, then-Minister of Education Bolduc asked the Advisory Board on English Education (ABEE) to advise him on how to encourage English-speaking youth to remain in Québec. In May 2016, Premier Couillard identified the English educational sector as a model for the system as a whole, and the Board proposed some reasons for this success in its most recent brief. It should be noted that students in the English sector achieve this success while receiving instruction in two languages from kindergarten onward. The ability to function in two languages is recognized as a crucial socio-economic skill for young Anglophones, and has an impact on their decision whether or not to stay in Québec. How can the education system contribute to developing this skill? This brief is respectfully presented to the Minister of Education with recommendations that respond to this question.

Bilingualism Essential for Evolution of Our Laws and Access to Justice for English and French-speaking Minority Communities - Quebec Community Groups Network (QCGN) (2015)

Youth Development Initiatives - Coasters Association (2015)
The Coasters Association has had many achievements over the years regarding youth initiatives, and priority areas have been identified. These achievements have contributed to the development and vitality of the region’s communities; however, there are many challenges that remain to hinder the future development and sustainability of the region.

Partnering for the Well-being of Minority English-Language Youth, Schools & Communities - Gonsalves, Allison; Kueber, Russell; Langevin, Paule; Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2015)
This document identifies some of the unique challenges, strengths, and aspirations of English-speaking youth in Quebec and provides a school and community-based framework for action intended to have a positive impact on their well-being and educational success. It emerges from the collaboration of community health and social services networks, called (NPIs) - abbreviation for the Networking and Partnership Initiative and Community Learning Centers (CLCs) seeking to improve the overall well-being of minority language youth residing in province.
Keywords: Official Language Minority Community (OLMC)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2015)

One Size Does Not Fit All: Distinct Solutions for Distinct Needs - Advisory Board on English Education (2013)
In this report to the Minister, the Advisory Board on English Education is taking the opportunity to review the themes and concerns identified in earlier correspondence, reports and briefs that continue to describe English education in Québec accurately, and to update them with current examples of both concerns and successes. We emphasize that there is no intention to promote one system over another, nor to assign fault. We believe that many of the inherent difficulties faced by English school boards, schools and centres could be mitigated if MELS were to take better account of the differences between the two sectors in its policies and their implementation. It is hoped that a description of the distinctiveness of the English sector and how it functions differently from the French sector will provide some insight as to how the English system is frequently constrained by many of the Ministry’s policies, especially in their application, and indicate the need for flexibility in implementing policy. This will ensure that the English education system can continue to prepare its graduates to participate fully in the life of Québec society.

Canada, Bilingualism and Trade - Arcand, Alan; The Conference Board of Canada (Community Economic Development and Employment Corporation (CEDEC), 2013)
The French language is one of the world’s major languages. According to L’Organisation internationale de la Francophonie (OIF), at least 220 million people in the world speak French. It’s the official language of all United Nations agencies and a large number of international organizations. The language originated in France and spread by way of the country’s overseas expansion. Today, some 30 countries in the world, including Canada, have recognized French as an official language.

Marking Milestones - English Language Arts Network (ELAN) (2011)

Media Statement - Alliance Quebec (AQ) (2003)

AQ Announces Initiative Against Bill 171 - Alliance Quebec (AQ) (2001)

AQ Opposes Language Laws Which Prohibibt the Sale of Children's Toys Based on the Language That These Toys Speak - Alliance Quebec (AQ) (2000)

AQ Calls on the Provincial Government to Guarantee Bilingual Status for All Districts that Would be Eligible as Autonomous Municipalities - Alliance Quebec (AQ) (2000)